ANALISIS KINERJA PORTOFOLIO DENGAN METODE SHARPE, TREYNOR DAN JENSEN PADA SAHAM JII 70 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nur Sa’diyah; Arfina Rahma; Herlina Agustina; Nurlia Nurlia; Dwi Taufik Rohman; Juwari Juwari (Fakultas Ekonomi Universitas Balikpapan, 2023)
The purpose of this study was to determine whether the single index method would produce an optimal portfolio of JII 70 shares and continued with assessing its performance using the Sharpe, Treynor and Jensen methods to determine the best method for assessing the performance of the formed stock portfolio. The data used is data in the form of closing prices obtained from the Indonesia Stock Exchange website. The number of samples used is 58 of the 70 stocks that are incorporated in JII 70. The sample selection is based on predetermined criteria. The data analysis tool used is Microsoft excel 2019. From the results of data processing, the results obtained are as many as 25 stocks that are included in the optimal portfolio using the single index method. After that, it is known that the best method for assessing portfolio performance is the Sharpe method.